Ladybird Histories :The Vikings - Bingham, Jane
Ladybird Histories is a series of books about periods and people in history that children find especially engaging and that are often taught in schools. Packed full of interesting and entertaining details that will delight all readers—from lifestyles, battles, and important characters to the influence the past has played on the world around us today. This Ladybird Histories title is all about the Vikings: their famous leaders, what people wore, how they lived, their fascinating myths and legends, and how they shaped Britain today. It has everything you need to know about the Vikings for school homework!